Preparation and Characterization of PLGA Microspheres Loaded by Cyclosporine-Cyclodextrin Complex: Preparation of cyclosporine loaded microspheres - Malaekeh-Nikouei, Bizhan; Sajadi Tabassi, Sayyed A.; Jaafari, Mahmoud R.; Davies, Nigel M. (Iranian Journal of Pharmaceutical Sciences, 2005)
The purpose of this study was to prepare and characterize microspheres loaded by cyclosporine A(CyA)-cyclodextrin (CD) complex. To achieve this goal, PLGA microspheres loaded by CyA-CD complex were prepared by multiple emulsificationsolvent evaporation methods. Morphology, size, encapsulation efficiency and drug release from these microspheres were evaluated. Microscopic evaluation of microspheres showed that microspheres were spherical in shape. The size analysis results indicated that size range varied from 1 to 50 mm for complex loaded microspheres. Encapsulation efficiency of microspheres was increased by increasing drug to polymer ratio. Drug release was found to be biphasic with a first more rapid release phase (burst) followed by a slower phase. After two weeks, 43.40%±3.45 of CyA was released from these microspheres. In conclusion, microspheres loaded with CyA-CD complex were prepared that could be used for control delivery of CyA.